2012
DOI: 10.1007/s00586-012-2179-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the small leucine-rich proteoglycans of pathological human intervertebral discs

Abstract: Purpose Proteoglycans are important to the functioning of the intervertebral disc. In addition to aggrecan there are the small leucine-rich proteoglycans (SLRPs). These are less common but in other locations their functions include collagen organisation, sequestering growth factors and stimulating inflammation. We have performed a comparative analysis of the SLRP core protein species present in intervertebral discs with various pathologies. Methods Eighteen intervertebral discs from patients with scoliosis (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…The current results showed that DCN transfection was able to significantly elevate the expression level of p15. Within cells, TGF-β binds with TGF-βRII to further phosphorylate TGF-βRI (18). The present study results showed that DCN transfection increased the expression level of TGF-βRII.…”
Section: A B C Dsupporting
confidence: 64%
See 2 more Smart Citations
“…The current results showed that DCN transfection was able to significantly elevate the expression level of p15. Within cells, TGF-β binds with TGF-βRII to further phosphorylate TGF-βRI (18). The present study results showed that DCN transfection increased the expression level of TGF-βRII.…”
Section: A B C Dsupporting
confidence: 64%
“…The TGF-β signaling pathway is able to inhibit the cell proliferation and differentiation at the early disease stage. However, at the later stage, TGF-β gradually loses its inhibitory effects, and thus promotes tumor metastasis (18). The present study results revealed that DCN enhanced TGF-βRII expression, promoting the TGF-β signaling pathway, which may represent the early event in the disease pathogenesis.…”
Section: A B C Dmentioning
confidence: 62%
See 1 more Smart Citation
“…Several SLRPs are known to occur in human discs and include biglycan, decorin, fibromodulin, keratocan and lumican [2326]. In addition, some of these SLRPs have been shown to be increasingly fragmented with disc degeneration in humans [23], as well as in the discs of chondrodystrophoid breeds of dog, which are prone to disc disorders [27]. In addition to aggrecan, decorin and biglycan in particular have been shown to influence nerve growth and function.…”
Section: Introductionmentioning
confidence: 99%
“…Although others report on similar processes such as fragmentation of certain SLRP (small leucine-rich proteoglycans) core proteins (e.g., bigylcans, lumican) in pathological tissues from patients with scoliosis, DDD and herniations, which are important for organization of collagen fibres and hence the structure of the extracellular matrix, the origin of these pathologies is different [25]. Moreover, there is evidence that these are involved in regulating inflammatory pathways [25]. Dudli et al reported on up-regulation of matrix remodelling genes being stable within 28 days following burst fractures in rabbits [26].…”
Section: Discussionmentioning
confidence: 96%